2021
DOI: 10.1029/2021ef002150
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Evaluation of Drought in CMIP6 Simulations

Abstract: About half of the Earth's land area is drought prone (Kogan, 1997) and an average of 55 million people around the world are affected by drought every year (Vatter et al., 2019). During 1900-2011, more than 11 million people lost their lives and two billion people were affected by drought (Spinoni et al., 2014). Droughts may further trigger other calamities such as wildfires and heatwaves (LeComte, 2011;Sivakumar, 2005). Unlike other disasters, such as floods or earthquakes, drought is a slowly developing pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 88 publications
1
18
0
Order By: Relevance
“…Given the main importance of precipitation on the severity of different drought types, this needs to be taken into account when assessing the goodness of future drought projections. Furthermore, the CMIP6 models exhibit significant bias in low precipitation values [ 99 ], which are the most relevant for assessing meteorological droughts.…”
Section: Global Drought Projectionsmentioning
confidence: 99%
“…Given the main importance of precipitation on the severity of different drought types, this needs to be taken into account when assessing the goodness of future drought projections. Furthermore, the CMIP6 models exhibit significant bias in low precipitation values [ 99 ], which are the most relevant for assessing meteorological droughts.…”
Section: Global Drought Projectionsmentioning
confidence: 99%
“…, with 0 indicating perfect match while the larger the E H distance (tending to 1), the more the mismatch (see Papalexiou et al, 2021 for a drought analysis using H distance).…”
mentioning
confidence: 99%
“…At present, the CMIP has evolved to the sixth phase (CMIP6), in which some improvements have been made in physics processes and model resolutions (Eyring et al, 2016). Some recent studies have started to use the CMIP6 simulations for the evaluation and projection of drought (e.g., Cook et al, 2020;Papalexiou et al, 2021;Wang et al, 2021;Yang et al, 2021). Wang et al (2021) revealed that the CMIP6 has high simulation accuracy at midlatitudes for drought analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2021) revealed that the CMIP6 has high simulation accuracy at midlatitudes for drought analysis. However, Papalexiou et al (2021) showed that no single model can perform better over a large region. Therefore, the challenge of coarse resolutions has discouraged some researchers from using GCMs.…”
Section: Introductionmentioning
confidence: 99%